Oportunidades y amenazas de un acuerdo Mercosur-CAN para Argentina y Brasil - CEI - Centro de Economía Internacional (Buenos Aires) (Centro de Economía Internacional (CEI), 2003)
– Trade between the countries of the Andean Community (AC) and Mercosur showed a positive trend throughout the nineties, although it slowed down in the second half of the decade and beginning of this decade. It can also be seen that if trade flows between the AC and Mercosur are adjusted according to the share of their respective countries in world trade, the trade exchange level between both blocks has not shown any significant changes during the last ten years. This means that integration did not go beyond the change in the share of these countries in the world's economy. Recent history shows that Argentina stands out in the trade relationship between Mercosur and CAN as the only Mercosur member shifting away from the Andean countries, which throughout the nineties lost their share both in Argentine exports as well as imports. In the other Mercosur countries the opposite is found to be the case. As a section of the Harmonized System, Mercosur exports to the AC show much higher diversification than AC sales to Mercosur, which even show greater concentration than is found in its sales to the rest of the world, as is the case with mineral fuels. Although the AC accounts for 7% of Argentine exports outside Mercosur, the Andean countries are an important destination for several product groups. As far as Argentina is concerned, the AC accounts for 14-17% of Argentina's extra-Mercosur sales of Chemicals, Plastics and rubber, Machinery and Equipment and Base metals and their manufactures. A similar development is found in Brazil for the first three as well as in Textiles and their manufactures. Since the tariff liberalization process in both blocs is far from being complete (except in the case of Bolivia, which signed a broad liberalization agreement with the countries of Mercosur), the question arises as to how the elimination of tariffs between the two large blocs of South America could lead to deeper trade integration.
Keywords: 330; Handelsabkommen; Internationale Wirtschaftsbeziehungen; MERCOSUR-Staaten; Andenpakt-Staaten; Argentinien; Brasilien